Application of Diverse Silicon Sources to Soil for Reducing Wheat Blast Disease - Setu, Fahmida Farzana; Rahman, Md Arifur; Sarker, Md Zahirul Islam; Uddin, Md Kafil; Ahmed , Istiaq; Mohiuddin, K M (Journal of the Bangladesh Agricultural University, 2024)
Despite the economic potential of wheat for food security, blast disease is one of the major constraints to wheat production in warm and humid areas. Silicon (Si) increases crop yields and resistance to both biotic and abiotic stresses. The effect of various Si sources, including Na2SiO3, MgSiO3, CaSiO3, and rice hull ash (RHA), on suppressing wheat blast (WB) incidence was studied at Bangladesh Institute of Nuclear Agriculture field from November 2019 to March 2020 using a complete randomized design (CRD) with three replications. Total 42 plastic pots were filled with the recommended doses of fertilizers and Si. On 17 days after inoculation (DAI), the lowest WB incidence (83.16%) and severity matrix (80.20%) were found with the treatment of CaSiO3 @ 100 kg ha-1. At 15 DAI, the same treatment reduced the WB incidence and severity matrix by 21.10% and 41.73%, respectively. Most yield indicators were significantly improved by the Si fertilizers, except for grain spike-1 quantity, weight, and thousand grain weight (g). However, pots that were fertilized with Si distinguished out from both the control and absolute control groups. While CaSiO3 at 75 kg ha-1, RHA at 6.0 t ha-1, and MgSiO3 at 100 kg ha-1 produced respectable yields, the maximum was achieved by CaSiO3 at 100 kg ha-1. There was a significant positive relationship between the leaf concentrations of K and Si, with the highest concentration found in plants treated with CaSiO3. A large number of yield metrics showed moderate to strong positive associations with leaf K and Si concentrations, whereas the disease severity matrix revealed the maximum significant negative correlation with these elements. The best outcomes were obtained by applying Si as CaSiO3 @100 kg ha-1, which has potential as an environmentally acceptable source for controlling WB disease and increasing wheat yields. J Bangladesh Agril Univ 22(3): 295–309, 2024